NMR studies of cbEFG-like domains from human fibrillin-1 - Smallridge, R; Rachel Sara Smallridge (2000)
﻿ The calcium binding epidermal growth factor-like (cbEGF) 12-13 domain pair from human fibrillin-1 was the focus of studies for this dissertation. Various nuclear magnetic resonance (NMR) spectroscopy techniques were employed to analyse the calcium binding, structural and dynamic properties of this pair, and to assess the effects of a disease-causing mutation. Fibrillin-1 is a mosaic protein composed mainly of 43 cbEGF domains arranged as multiple, tandem repeats, and mutations within fibrillin-1 have been linked to Marfan syndrome (MFS). 66% of MFS-causing mutations identified thus far are localised to cbEGF domains, emphasising that the native properties of these domains are critical to the functional integrity of this protein. The cbEGF 12-13 pair is found within the longest run of cbEGFs in fibrillin-1, and many mutations that cluster in this region are associated with the severe, neonatal form of MFS. It is thought that this region may be important for fibrillin-1 assembly into 10- 12nm connective tissue microfibrils. Calcium binding studies of cbEGF 12-13 demonstrated that cbEGF 13 contains the highest affinity site thus far investigated from human fibrillin-1. Comparison with previous results showed that fibrillin-1 cbEGF calcium binding affinity can be significantly modulated by the type of domain which is linked to its N-terminus, and also highlighted the high affinity of the "neonatal" region. The NMR solution structure of cbEGF 12-13 is a near-linear, rod-like arrangement of two cbEGF domains, with both exhibiting secondary structure characteristic of this domain type. The rod-like arrangement is stabilised by calcium binding by cbEGF 13 and by hydrophobic interdomain packing interactions. This observation supports the hypothesis that all Class I EGF/cbEGF-cbEGF pairs, characterised by a single linker residue, possess this rod-like structure. The structure also exhibits additional packing interactions to those previously observed for cbEGF32- 33 from fibrillin-1, which may explain the higher calcium binding affinity of cbEGF13. A model of cbEGF 11-15, created based on structural data for cbEGF 12-13 and a model of cbEGF32-36, has highlighted a potential protein binding interface, which encompasses all known neonatal MFS mutations, as well as a flexible, unstructured loop region of cbEGF 12. Backbone dynamics data confirmed the extended structure of cbEGF 12-13. These data, combined with previous data for cbEGF32-33, highlighted a potential dynamics signature for Class I cbEGF domain pairs. Comparison of data for these pairs also suggested that, in addition to the role of calcium in stabilising rigidity on the picoto millisecond time-scale, calcium affinity may play a key role in determining the anisotropy of cbEGF pairs. Possible dynamic explanations for the variation in calcium binding affinity of cbEGF domains from human fibrillin-1 were also noted. The Gl 127S mutation located in cbEGF 13 of fibrillin-1 causes a mild variant of MFS. NMR studies of the G1127S cbEGF12-13 mutant pair showed that cbEGF12 may chaperone folding of mutant cbEGF 13, an effect most likely mediated through interdomain packing interactions. These studies have also shown that the effects of this mutation are localised to cbEGF13, suggesting that a "partial" MFS phenotype is the result of altered structural, dynamic and/or calcium binding properties of this domain.